Інтелектуальний капітал економіки знань - Поплавська, Ж.В.; Поплавський, В.Г. (№2, 2007)
Radical changes in the modern society and the models of future enterprise caused value creation in knowledge containing economy. From today knowledge has become the main source of nation prosperity that not only generates but also forms a new value turning into a motive power of economic growth.